STUDY ON THE EFFECT OF WATER CONTENTS IN THE DISTRIBUTION TRANSFORMER OIL AGAINST IT'S BREAKDOWN VOLTAGE - Manurung, Daniel Julius Pangihutan; Kurnianto, Rudi; Rajagukguk, Managam (Faculty of Engineering, Universitas Tanjungpura, 2024)
The degradation of electrical power quality due to high water content in transformer oil is a critical issue because water in transformer oil can cause insulation degradation, increase electrical conductivity, and accelerate the corrosion process of internal components. This results in a decrease in transformer performance and reliability, and increases the risk of electrical faults or failures that can have far-reaching impacts on the power distribution network. Water damage can also shorten the operational life of the transformer and increase maintenance and component replacement costs. Therefore, testing the breakdown voltage, moisture content, and flash point of distribution transformer oil is very important to determine the feasibility of transformer oil. This study aims to determine the effect of moisture content on breakdown voltage and flash point, as well as the effect of breakdown voltage on flash point. By using the test method of breakdown voltage, moisture content, and flash point is expected to determine the feasibility of transformer oil. The results obtained from the old transforamtor oil (14 years) have a breakdown voltage of 1.3 kV, the transformer oil has been used (2 years) of 24.25 kV, and for the new transformer oil of 34.4 kV. For old transformer oil moisture content of 140.19 ppm, used transformer oil moisture content of 34.03 ppm, new transformer oil moisture content of 26.04 ppm, old transformer oil flash point measurement results of 148 ° C, used transformer oil samples of 150 ° C, and new transformer oil samples of 160.5 ° C. In conclusion, the old and new transformer oil is still suitable for use.